Ruxolitinib as an Effective and Steroid-Sparing First-Line Treatment in Newly Diagnosed BOS Patients After Hematopoietic Stem Cell Transplantation - Zhang, Xiaoyu; Zhao, Xiaoli; Shen, Yuyan; Shi, Yuanyuan; Zhang, Lining; Hao, Mengze; Zhao, Fei; Zhang, Rongli; Wei, Jialin; Feng, Sizhou; He, Yi; Jiang, Erlie; et al. (Frontiers in Pharmacology, 2022)
Bronchiolitis obliterans syndrome (BOS) is a life-threatening pulmonary complication of chronic graft versus host disease (cGVHD) after allogeneic hematopoietic stem cell transplantation (HSCT). In this study, we retrospectively identified seven patients newly diagnosed with BOS post HSCT and analyzed the outcomes in those patients treated with ruxolitinib as a first-line treatment. All seven patients achieved symptoms responses within two weeks after ruxolitinib administration. Three months after treatment, five patients (71.43%) achieved a CR, and two (28.57%) achieved a PR. The overall response rate (ORR) was 100%. Additionally, the steroids therapy was determined within two months after ruxolitinib treatment, indicating ruxolitinib as a steroid-sparing agent. We also found that ruxolitinib was well tolerated and safe in treating newly-diagnosed BOS. According to our results, ruxolitinib would be a promising and safe option in newly-diagnosed BOS post-HSCTIntroduction.